Answer:
see below
Step-by-step explanation:
-33, -27, -21, -15,....
-33 +6 = -27
-27+6 = -21
-21+6 = -15
This is an arithmetic sequence
The common difference is +6
explicit formula
an=a1+(n-1)d where n is the term number and d is the common difference
an = -33 + ( n-1) 6
an = -33 +6n -6
an = -39+6n
recursive formula
an+1 = an +6
10th term
n =10
a10 = -39+6*10
= -39+60
=21
sum formula
see image
The sum will diverge since we are adding infinite numbers
Base = 2 x height (b = 2h)
Area = 1/2 x base x height = 1/2 x 2h x h = h x h = h^2
Answer:
Step-by-step explanation:
Perpendicular means that the slopes of the "old" line and the "new" line are opposite reciprocals; bisector means that the "new" line goes directly through the center of the "old" line. This perpendicular bisector, then, will go directly through the center of the "old" line, cutting it directly in half and leaving in its wake a 90 degree angle. To write this equation, then, of the perpendicular bisector, we need the slope of the old line and the midpoint of the old line. Let's work on the midpoint first:
So the "new" line will go through this point.
Onto the slope:
so the slope is
m = -4. That means that the perpendicular slope is
Now we're ready to write the equation:
and
and finally,
![y=\frac{1}{4}x+\frac{17}{4}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B1%7D%7B4%7Dx%2B%5Cfrac%7B17%7D%7B4%7D)
Answer:
12.566368 units
Step-by-step explanation:
2(pi)r = C
2(pi)(2) = C
4(pi) = C
4(3.141592) = C
12.566368 = C
Probably A I am not really sure I am trying sorry if it is wrong